Analisa Aspek Moral dan Budaya dalam Pemajuan Hak Kekayaan Intelektual - Gunawan, Yusuf (PT Elaborium Elevasi Indonesia, 2025)
Intellectual Property Rights (IPR) play a crucial role in protecting individual creations and fostering innovation in Indonesia. However, public awareness of the importance of IPR remains low, leading to widespread practices of piracy, plagiarism, and unauthorized use of creative works. This study analyzes the moral and cultural aspects influencing IPR protection in Indonesia and examines how existing regulations, such as Law No. 28 of 2014 on Copyright, can be implemented more effectively. The findings indicate that the culture of sharing and the limited understanding of creators' moral rights pose significant challenges to the advancement of IPR. Furthermore, technological developments have accelerated the dissemination of creative works while also increasing the potential for IPR violations. Therefore, continuous education efforts and collaboration between the government, academia, and industry are essential to raising public awareness and fostering respect for IPR. With the right approach, Indonesia’s IPR protection system can be strengthened to support creativity and innovation across various sectors.